Investigation of attributes influencing the attractiveness of mobile commerce advertisements on the facebook platform - Donatas Cvirka; Elzė Rudienė; Mangirdas Morkūnas (Economies, 2022)
Examining and analyzing the determinants facilitating consumers' intention to buy via mobile commerce platforms have untapped potential when it comes to advertisement potential and perceived advertising value. Therefore, this paper examines various aspects of the advertisements on mobile commerce platforms and analyzes the importance of intention to buy. The goal of the article is to analyze and determine which aspects of the advertisements have an influence on expediting purchase through mobile commerce. The underlying hypothesis for this investigation is the applicability of the perceived advertising value of mobile commerce, positively associated with attitude towards advertising channels. The Facebook social network has been chosen as an advertisement channel as it is the most popular and biggest investment-generated channel. It is also proven that subjective norms are positively associated with the intention to buy via mobile commerce. This, combined with perceived advertising values and attitudes towards Facebook ads on mobile commerce, influenced the intention to buy.
Keywords: 330; advertisement; Facebook; intention to buy; mobile commerce